Synthesis and self-assembly of corona-functionalised polymeric arsenical nanoparticles. (5th February 2021) - Tobin, Hayden; Liarou, Evelina; Song, Ji-Inn; Magiakos, Alexandros; Wilson, Paul
Graphical abstract: Highlights: Simplified route to corona-functionalized block copolymeric arsenical nanoparticles. Stable nanoparticles are easily formed by direct dissolution in MilliQ water. [AsAm] affects the stability, morphology and toxicity of the nanoparticles. Additional stabilization and modification of this nanoparticle system possible. Abstract: Polymeric arsenicals are emerging as an interesting platform for functional and (re)active materials in the field of polymer and (bio)materials science. Through exploiting the diverse and distinct reactivity of organic arsenicals in As(V), As(III) and As(I) oxidation states efficient methods for bioconjugation as well as hydrogel and nanoparticles formation have been reported. Here we expand on this body of work by reporting the synthesis of new amphiphilic block copolymeric arsenicals with a target composition of P((DMAm100-X -co -AsAmX )- b- DAAm100 ) (P1, X = 0; P2, X = 5; P3, X = 20) which form nanoparticles (NP1 –NP3 ; D h = 49–71 nm) upon self-assembly in water. The mole fraction of the AsAm monomer appears to have an effect on the particle morphology and stability, with stability decreasing as a function of the AsAm mole fraction in the corona. The reactivity of the AsAm (As(V)) group has been exploited to modify the corona functionality via direct reduction (NPRed ) and sequential reduction and thiol substitution (NPGSH ) . The resulting As(III)-functionalised nanoparticles (NPRed ) exhibited concentration-dependent toxicity against human prostate adenocarcinoma epithelia cell (PC-3) alluding to future development of these particles for mono- or combination therapy within appropriate nanoparticle formulations.